Kastek and Rgayty passes in written sources (Journal of history, 2022)
The article talk about the mountain passes of Kastek and Yrgayty, related to the complex and dangerous parts of the caravan roads of the Antiquity and the Middle Ages. Between Kastek and Zhetizhol Ridges in the spurs of Tien Shan (Khan Tengri Mountains) is Kastek Pass and Rgaiti Pass between Zhetizhol and Atzhailau Mountains. Caravan or migration paths passed through the Kastek Pass from the Shu region to the Ily Valley, through the Rgayty Pass from the Shu region along the Shu-Ili mountain, and overlook the western end of Balkhash Lake. The names of mountains and passes in this region, found in written sources, and their etymology are discussed in more detail. The origin of the names “Kara-Kasmak,” “Arjatu,” “Urun-Arj,” found in written sources, is analyzed. An overview is also given of the meaning of the names of the Uisun tribes that inhabited this territory in ancient times, “Uosuәn,” “Oswan,” “Asien,” “U-suni = Asian,” “Usun” (“Wusun”), found in written sources. The data identified on the basis of archaeological exploration work conducted by the author in recent years in this region are analyzed in terms of new data on the Kastek and Rgaity passes. The author gives an overview of the history of studying ancient caravan roads and medieval monuments along with them, and shows the features of the topographic location of archaeological sites discovered in recent years. During the article, the names of the passes through which the caravan routes passed are etymologically revised, and the names “Usun Alatau” and “Usun Pass” are proposed on the basis of written data.